Implementation of brain gym and puzzle therapy and changes in cognitive function among elderly people with dementia in primary health care: A descriptive case study - Lisdahayati Lisdahayati; I Gusti Ayu Putu Desy Rohana; Saprianto Saprianto; Gunardi Pome; Umar Hasan Martadinata; Eldi Fajriansyah (Lentera Perawat, 2026)
Background: Dementia is a progressive decline in cognitive function that affects memory, thinking, behavior, and activities of daily living, particularly among older adults. The increasing proportion of the elderly population has contributed to the rising burden of cognitive impairment, emphasizing the need for accessible non-pharmacological interventions in primary healthcare settings. Brain gym and puzzle therapy are cognitive stimulation approaches that may support cognitive function among older adults with mild cognitive impairment. Objective: This study aimed to describe changes in cognitive function among older adults before and after the implementation of brain gym and puzzle therapy. Methods: A descriptive case study was conducted in the working area of Tanjung Agung Primary Health Center, Ogan Komering Ulu Regency. Two older adults were selected using purposive sampling based on the inclusion criteria: aged 60 years or older, having mild cognitive impairment based on Mini-Mental State Examination scores, and willingness to participate in the entire intervention program. The intervention was delivered by a nurse with family members acting as caregivers over four weeks. Each session was conducted daily for 30–45 minutes, consisting of 10–15 minutes of brain gym followed by 20–30 minutes of puzzle therapy. Cognitive function was assessed before and after the intervention using the Mini-Mental State Examination and the Short Portable Mental Status Questionnaire. Data were analyzed descriptively. Results: The Mini-Mental State Examination scores increased from 18 to 24 in participant 1 and from 17 to 23 in participant 2. The Short Portable Mental Status Questionnaire error scores decreased from 5 to 3 and from 6 to 3, respectively. Additional improvements were observed in the participants’ ability to follow instructions, active participation, and speed of puzzle completion. Conclusion: Brain gym and puzzle therapy may contribute to improved cognitive function among older adults with mild cognitive impairment. These interventions can be considered as feasible non-pharmacological nursing strategies in gerontological care within primary healthcare settings.